(untitled) (Quinto Sol, 2018)
This paper analyzes the conflictive implementation of freedom of the press in Buenos Aires, after the fall of Rosas’ regime. It examines norms and the initiatives to reform them, some trials, government actions, and the debates within the legislature and the press. The study discusses the traditional interpretation according to which, in the province of Buenos Aires, those years were characterized by a wide freedom of expression. It also argues that the difficulties to implement freedom of the press in the 19th century are explained by the tension between the consideration of the press as a pillar of civilized, republican societies and, at the same time, as a corrosive agent of the social and political order.